A hybrid method for improving quality of service in constraint-based availability in the cloud for SMEs. (10th May 2019) - Koupaei, Alireza Nik Aein
Research in cloud computing has gone through rapid development during the last decade and has emerged as a key service of utility or on-demand computing. Small and medium-sized enterprises (SMEs) assure economic growth in the world. In the main, many SMEs are struggling to survive in an ongoing global recession and are often unwilling to use research results and new technologies for business and learning. Cloud computing provides many opportunities and could help companies expand and improve their business and use technology more resourcefully. The resource provision is an essential perspective of cloud computing technology to provide the quality of service (QoS) in cloud computing. It is used as an alternative to service level agreement (SLA). In this paper, we are going to present a new cloud hybrid method and architecture to improve, the QoS and availability under the cloud computing environment. Additionally, issues regarding the extent effect of cloud computing in SMEs have been highlighted. In conclusion, critical future challenges in the area are addressed.